Multisensory’s Approach to Stimulate Child Early Literacy Ability - Cut Citra Novita; Juhairiah (JOYCED: Journal of Early Childhood Education, 2021)
This research is a literature study that aims to stimulate early literacy in early childhood through a multisensory approach. This research is a descriptive qualitative type using literature study, with a background of low initial reading skills, the concern that parents are concerned about their children who cannot read when they enter elementary school, and the development of a literacy culture. In this literature study research, researchers used various written sources such as articles and documents relevant to this research. In this study’s literature study, there was an increase in literacy, both from preface reading and initial writing, with a multisensory approach—the results of several studies that a multisensory approach can improve early reading and writing for early childhood.